Penyelesaian Ganti Rugi Atas Kecelakaan Kapal di Indonesia dalam Perspektif Tanggung Jawab Perdata - Achmad Jauhari (Syntax Corporation Indonesia, 2024)
Two formulations of problems in this study, namely: (1) What are the results of civil liability analysis in settling compensation for ship accidents in Indonesia. (2) How does the judge's judgment through the District Court Decision compare with the Shipping Court Decision on the case. The type of research raised is Normative Juridical Research (literature law research). The source of data in this study is secondary data. Secondary data are data obtained from literature studies. Secondary data in the field of law viewed from the point of binding strength can be divided into 3 (three), namely primary legal material, secondary legal material, and tertiary legal material This research uses a case approach (case appoarch) and a legal approach (statua appoarch). The analysis method used is a qualitative normative method, namely research by describing conditions and facts about the object of research. The results of this study, namely, the Perspective of Civil Responsibility in the Settlement of Compensation for Ship Accidents in Indonesia (Case Study of District Court Decisions and Shipping Court Decisions) can be concluded that the Shipping Court Decision is only limited, that is, it does not mention the compensation of Shipping Companies to the owner of the goods, because the competence and jurisdiction possessed by the Shipping Court is very limited.